Rational design of novel Plasmodium falciparum glutamyl-tRNA synthetase inhibitors for the development of next-generation antimalarial drugs - Wesam Nofal (PLoS ONE, 2025)
A major obstacle in treating malaria is the emergence of antimalarial drug resistance. The aminoacyl-tRNA synthetases (aaRSs), which are essential enzymes for protein synthesis, have been identified as potential targets for the discovery of anti-parasitic drugs. Of these, Glutamyl-tRNA synthetase (GluRS) is a crucial aaRS enzyme in Plasmodium falciparum and is a vital therapeutic target. In this study, potential GluRS inhibitors are reported from the Medicinal Fungi Secondary Metabolites and Therapeutics (MeFSAT) chemical library using structure based virtual screening via PyRx v0.8. To evaluate the stability of top hit protein-inhibitor complexes, molecular dynamics simulations (time period, 100 ns) were performed from an initial batch of 1,830 compounds. The two shortlisted compounds, MSID000152 and MSID000974, showed the strongest negative binding affinities of −10.4 kcal/mol and −10.1 kcal/mol, respectively. For comparative analysis, Chloroquine was used as a control to validate the screening results. The dynamics of both complexes showed stable structure, with mean RMSD of 3.94 Å for MSID000152, 2.35 Å for MSID000974, and 2.39 Å for chloroquine. The MSID000152 illustrated favorable MMPB/GBSA binding free energy. Taken together, the study highlights MSID000152 and MSID000974 as promising antimalarial lead compounds for additional in vitro and in vivo investigations.